Little Reminder: Daily Du’as for Kids – An Interactive AR-Based Learning Book in Islamic Study for Preschool - Zaimi, Rahimah (IRC, 2019)
This research paper presents the background of Augmented Reality (AR) and how it contributed to the cahnges in technology.